GAINING FACE OR LOSING FACE? FRAMING THE DEBATE ON FACE TRANSPLANTS - Huxtable, Richard (Bioethics, 2005)
An American surgical team has announced its intention to perform the first human facial transplantation. The team has, however, invited further analysis of the ethical issues before it proceeds and in this paper we take up that challenge in seeking to frame the debate with a particular focus on the recipients of the transplant. We address seven related areas of concern and identify numerous questions that require answers or, perhaps, better answers. We start by examining the nature of the procedure and its intended benefits, why the procedure is being developed, and whether or not this should be viewed as experimental. Having concluded that this is experimental in nature, we then consider the broad question, who is the patient? Here we perceive difficulties in terms of the autonomy of the recipient, the unpredictable effects of receiving the transplant, and the role and influence of society. We conclude by asking whether the question should be ‘whether or not?’ rather than ‘when?’, particularly while the risks of losing face appear to far outweigh the likelihood of gaining face.